Relationship between Teacher Communication and Students Against Learning Outcomes in Al-Qur'an Hadist Class 7 MTsN 3 Bogor: Hubungan Komunikasi Guru dengan Siswa Terhadap Hasil Belajar pada Mata Pelajaran Al-Qur'an Hadist Kelas 7 MTsN 3 Bogor - Siti Nurjanah; M. Dahlan R; Ahmad Shobari (IJER (Indonesian Journal of Educational Research), 2019)
The purpose of this study was to determine the relationship between teacher communication with students towards learning outcomes in the Al-Qur'an Subjects of the 7th grade Hadith 3 Bogor. This research method uses quantitative methods with data collection techniques, namely questionnaires, interviews, observation and documentation. The research site was conducted in Bogor State Islamic Elementary School (MTsN) 3 which is addressed in the integrated education complex of Bogor district.While the research time the author plans to start from January 6 to April 2019.The respondents of this study were determined randomly. Data collection by means of questionnaires are given to respondents who have been selected randomly, while the data collection technique is by interviewing teachers of MTsN 3 Bogor. Then the data that has been obtained is analyzed quantitatively by product moment statistical test with the help of MBS SPP. Research on the Relationship between Teacher Communication and Students Against Learning Outcomes in Al-Qur'an Subjects in the 7th grade Hadiths of Bogor 3, shows that there is a significant relationship between teacher communication with students on learning outcomes with a score of 0.421 based on a range of 0.400-0.599 which means related MEDIUM.